FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA KEPEMILIKAN JAMBAN KELUARGA DAN PERSONAL HYGIENE DENGAN KEJADIAN DIARE DI DESA SEI MUSAM KENDIT KECAMATAN BAHOROK KABUPATENLANGKAT TAHUN 2014 - faisal azwinsyah; Surya Dharma; Devi Nuraini Santi (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT One of health efforts in society is basic sanitation. One of basic sanitation facility in society is latrine. Latrine is useful for the dispose of human feces so the bacteria in the feces did not pollutes the environment and then environment is clean with good esthetic. This aim of this research is to study the factors realted to the few of ownership of household’s latrine and personal hygiene with diarrhea incidence in Desa Sei Musam Kendit, sub district of Bahorok, regency of Langkat. This research is analytic study with cross sectional study using the primary data was collected from the responden of household with questionnaire instrument and the secondary data from Puskesmas Bukit Lawang. The data was analyzed by analytic and statitical test with chi square test with 95% CI. The result of statistic analysis indicates that there is a significant correlation to the education and ownership of household’s latrine (p=0.049),the income ownership of household’s latrine(0,001),the knowledge on ownership of household’s latrine(p=0,002),the ownership of latrine with diarrhea incidence(p=0,002)and personal hygiene with diarrhea incidence (p=0,007).and there is a significant correlation between the attitudes and ownership of household’s latrine(p=0,095) and between the association ownership of household’s latrine(p=939). It is suggested to the people who lives in Desa Sei Musam Kendit to pay attention to personal hygiene and use the latrine that fulfill the health requirement to avoid the transmission of diarrhea and the health staff must provide the society with activity about the importance of personal hygiene, the ownership of household’s latrine and the importance of environment sanitation. Keyword : Characteristic, Knowledge, Ownership of latrine, Personal Hygiene, Diarrhea incidence.